Changes in the global, regional, and national burdens of NAFLD from 1990 to 2019: A systematic analysis of the global burden of disease study 2019 - Wang, Dan; Xu, Yanbing; Zhu, Zizhao; Li, Yanliang; Li, Xiaowen; Li, Yike; Shen, Hui; Wu, Wei; Liu, Yazhuo; Han, Cheng (Frontiers in Nutrition, 2022)
Background: Understanding the burdens and trends of non-alcoholic fatty liver disease (NAFLD) is necessary for developing effective intervention strategies. In this study, Global Burden of Disease (GBD) 2019 study data were extracted and analyzed to elucidate trends of NAFLD. Methods: The prevalence, incidence, disability-adjusted life year (DALY), and death rates of NAFLD in geographic populations worldwide from 1990 to 2019 were extracted from the GBD 2019 study data. The global temporal trend of NAFLD from 1990 to 2019 was evaluated using estimated annual percentage changes (EAPCs) and age-standardized rates. Results: Globally, between 1999 and 2019, the age-standardized prevalence rate of NAFLD increased, with EAPCs of 0.77 (95% CI [0.69, 0.85]), whereas the DALY and Death rates decreased, with EAPCs of −0.82 (95% CI [−0.92, −0.71]), and −0.67 (95% CI [−0.76, −0.58]), respectively. Geographically, the age-standardized prevalence rate showed the most serious upward trend in high-income North America with an EAPC of 0.98 (95% CI [0.95, 1.02]), and the age-standardized incidence rate showed an upward trend in Central Asia with an EAPC of 3.17 (95% CI [2.2, 2.49]). The most significant upward trend of DALY and death rates appeared in Eastern Europe, with EAPCs of 4.06 (95% CI [3.31, 4.82]), and 3.36 (95% CI [2.77, 3.96]), respectively. At the country level, the age-standardized rates showed an upward trend in Armenia, Belarus, and Republic of Korea.Regarding the sociodemographic index (SDI), the highest age-standardized prevalence, incidence, and Death rates of NAFLD occurred in middle-SDI countries, and the highest DALY rates of NAFLD occurred in low-SDI countries. Conclusion: Global NAFLD burdens have increased since 1990. Our findings provide a reference for policymakers to reduce the burden of NAFLD, especially in middle and low-SDI countries.